Selagintriflavonoids with BACE1 inhibitory activity from the fern Selaginella doederleinii. (February 2017) - Zou, Zhenxing; Xu, Pingsheng; Zhang, Guogang; Cheng, Fei; Chen, Kai; Li, Jing; Zhu, Weixing; Cao, Dongsheng; Xu, Kangping; Tan, Guishan
Abstract: Eight triflavonoids, selagintriflavonoids A-H, were isolated from whole herbs of Selaginella doederleinii . The structures of compounds selagintriflavonoids A-C consisted of three naringenin units, whereas those of selagintriflavonoids D-H consisted of apigenin and two naringenin moieties. The structures and absolute configurations of the compounds were determined based on NMR, HRESIMS, and experimental and calculated electronic circular dichroism (ECD) data. The ability of the compounds to inhibit β -secretase (BACE1) was also evaluated. All compounds exhibited BACE1 inhibition with IC50 values ranging from 0.75 to 46.99  μ M. Selagintriflavonoid A exhibited the strongest inhibition (0.75  μ M) and is thus a promising compound for treating Alzheimer's disease. Graphical abstract: Eight triflavonoids, selagintriflavonoids A-H were isolated from whole herbs of Selaginella doederleinii . Their structures were established by comprehensive spectroscopic analysis coupled with calculated electronic circular dichroism (ECD) data, and their BACE1 inhibitory activities were preliminarily tested. Highlights: Eight compounds with a trimeric skeleton were isolated and identified. Received compounds may be interesting from a medicinal point of view (Alzheimer's disease). Simultaneous use of NMR and ECD spectroscopy was employed to solve stereochemistries.